2004
DOI: 10.1128/mcb.24.12.5269-5280.2004
|View full text |Cite
|
Sign up to set email alerts
|

Erk/Src Phosphorylation of Cortactin Acts as a Switch On-Switch Off Mechanism That Controls Its Ability To Activate N-WASP

Abstract: The Arp2/3 complex can be independently activated to initiate actin polymerization by the VCA domain of WASP family members and by the acidic N-terminal and F-actin-binding repeat region of cortactin, which possesses a C-terminal SH3 domain. Cortactin is a target for phosphorylation by Src tyrosine kinases and by serine/threonine kinases that include Erk. Here we demonstrate that cortactin binds N-WASP and WASP via its SH3 domain, induces in vitro N-WASP-mediated actin polymerization, and colocalizes with N-WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
331
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(357 citation statements)
references
References 65 publications
21
331
3
2
Order By: Relevance
“…3A). Notable phosphorylation sites known to be involved in cell movement and enriched in the PD include ERK, ␣-parvin, and cortactin (SI Table 3) (24)(25)(26). These findings are consistent with a significant body of evidence showing that phosphorylation is a critical component that regulates cytoskeletal and focal adhesion-signaling dynamics during PD formation (3,17).…”
Section: Functional Comparison Of Phosphoproteins In the Cb And Pdsupporting
confidence: 76%
See 1 more Smart Citation
“…3A). Notable phosphorylation sites known to be involved in cell movement and enriched in the PD include ERK, ␣-parvin, and cortactin (SI Table 3) (24)(25)(26). These findings are consistent with a significant body of evidence showing that phosphorylation is a critical component that regulates cytoskeletal and focal adhesion-signaling dynamics during PD formation (3,17).…”
Section: Functional Comparison Of Phosphoproteins In the Cb And Pdsupporting
confidence: 76%
“…These substrates are known to be involved in cell migration. It is also notable that the ERK phosphorylation site identified in cortactin (Ser 405; SI Table 3) has been previously shown to play an important role in cell motility (24,25). Further analysis of the data set for proteins that contain both an ERK kinaserecognition sequence (P-X-[S T]-P) (35) and an ERK docking site ([R K]-X 2-6 --X-X, where indicates hydrophobic residues Leu, Ile, and Val) or a binding motif (F-X-F) (33) revealed 12 other possible ERK substrates, including the uncharacterized proteins KIAA0731 and FLJ4447 (SI Table 6).…”
Section: Characterization Of the Ras/erk-signaling Pathway In The Pd Bymentioning
confidence: 99%
“…In contrast, two extracellular signal-regulated kinase (ERK) sites located at Ser-405 and Ser-418 sites, and ERK phosphorylation enhances cortactin binding and activation of N-WASP (Huang et al, 1998;Campbell et al, 1999;Weed and Parsons, 2001;Martinez-Quiles et al, 2004). Recent studies using mass spectrometry have identified 17 new sites of phosphorylation (12 serine, 4 threonine and 1 tyrosine), suggesting that cortactin is heavily phosphorylated in vivo (Martin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…WAVE and cortactin colocalize with Arp2/3 complex in lamellipodia, and RNAi knockdown experiments indicate that both NPFs contribute to nucleation of actin filaments in these structures (26,58,59). WAVE contains one V region and as a dimer was found to have slightly higher activity than dimeric N-WASP-VCA but less activity than dimeric WASP VCA (Fig.…”
Section: The Distinct Modes Of Activation Of Arp2/3 Complex By Cortacmentioning
confidence: 99%
“…Therefore, it is unclear whether potent synergy with cortactin is a general feature of WASP family proteins and if so, whether the mechanism is conserved. Cortactin colocalizes with WASP family proteins such as N-WASP, WASP, and WAVE (Wiskott-Aldrich syndrome protein family verproline-homologous protein) in multiple branched actin networks, including in podosomes (25), at the leading edge of lamellipodia (26), and at sites of endocytosis (27). Determining how branched actin is assembled in each of these structures will require an understanding of how each WASP family protein coordinately regulates Arp2/3 complex with cortactin.…”
mentioning
confidence: 99%